THE IMPACT OF FINANCIAL LITERACY, INCOME, AND LIFESTYLE ON INVESTMENT DECISIONS THROUGH THE AJAIB APPLICATION - Ni Kadek Ayu Aryanti; Ni Ketut Purnawati (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Investment decisions are crucial for investors in allocating funds to achieve future profits. Many factors influence investment decisions, including financial literacy, income, and lifestyle. This study aims to examine the effect of financial literacy, income, and lifestyle on investment decisions through the Ajaib application. The research was conducted among students of the Management Bachelor's Program, Faculty of Economics and Business, Udayana University, class of 2021, with a sample size of 173 respondents using purposive sampling. The data collected in this study are quantitative and were obtained through a questionnaire. The data analysis technique used is multiple linear regression. The results indicate that financial literacy, income, and lifestyle have a positive and significant effect on investment decisions. These findings suggest that the better a person's financial literacy, income, and lifestyle, the higher the tendency to make sound investment decisions through the Ajaib application